Ugly town: Race, policy and people in Perth in the 1920's - Gorman, Sean (Sage, 2016)
In considering the historical treatment of Aboriginal Australians this paper will discuss the different spaces operating in Western Australia's South West in the late 1920s and the government policies that fed into them. These are the Moore River Native Settlement that is located some 100 km north of Perth and White City, a carnival sideshow located at the bottom of William Street on the banks of the Swan River in Perth. The 1905 Aborigines Act and a provision within that act known as the Proclamation of the Prohibited Area of Perth will be discussed. This will be done by comparing the ways that White City was seen by the government in the 1920s and how in recent years Northbridge has been regulated and discursively constructed. The intent is to look at how Aboriginal people have been treated over time and consider the social, historical and political forces that have shaped that construction.